Nordic Noir - Hill, Annette; Turnbull, Sue (Research Online, 2016)
Nordic noir is an emerging crime genre that draws on crime fiction, feature film, and television drama. The term Nordic noir is associated with a region (Scandinavia), with a mood (gloomy and bleak), with a look (dark and grim), and with strong characters and a compelling narrative. Such is the popularity of Nordic noir as a brand for crime that it can also, and somewhat confusingly, be associated with disparate, bleak dramas set in particular locations outside the Scandinavian region (Sweden, Denmark, Norway, Iceland, and Finland), such as Wales, Italy, France, Mexico, and the United States. As such, Nordic noir is a global brand that attracts transnational audiences, and at the same time, it is a genre that offers a specific style of storytelling that has the look and feel of a regional, moody, and compelling crime narrative. The approach to Nordic noir taken in this article analyzes the genre as multidimensional, involving production and institutional contexts, creative practices, and the practices of audiences and fans. The research uses empirical and theoretical analysis drawing on genre analysis, as well as production and audience studies, including qualitative interviews and participant observations with executive and creative producers, viewers, and fans. Nordic noir is not a fixed genre; rather, it is in a constant process of iteration as it mutates, hybridizes and migrates from one location to another, where it may be received and understood in different ways. The concept of "genre work" is useful in helping to capture and critically analyze Nordic noir from multiple perspectives, taking into account the complex ways in which this genre is a cocreation between industries and audiences. This is particularly evident in the case of the Danish-Swedish coproduction Broen/Bron/The Bridge (2011), which provides an illuminating case study of these processes at work. It is this constantly ongoing notion of genre work that illuminates the fluidity of Nordic noir, where its meaning and symbolic power is cocreated by institutions, producers, and audiences.